PHYTOCHEMICAL SCREENING, PHENOLIC COMPOUND CONTENT AND ANTIOXIDANT POTENTIAL OF THIRTEEN MEDICINAL PLANTS OF THE ROCKY OUTCROPS OF THE BOSQUE DE PIEDRAS OF HUARACA, PERU - Aronés Jara, Marco Rolando (2022)
The objective of this research was to perform the phytochemical screening, determine the content of phenolic compounds and evaluate the antioxidant potential of thirteen medicinal plants from the rocky outcrops of the Bosque de Piedras of Huaraca in Peru. Secondary metabolites were identified by phytochemical screening and the content of phenolic compounds included the quantification of total phenols (TPC), flavonoids (TFC) and anthocyanins (TAC). Antioxidant potential in the hydroalcoholic extract, expressed as mean inhibitory concentration (CI50), evaluated at 100 µg/mL, was performed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The results show that flavonoids, phenols and/ or tannins were present in all thirteen species. Brachyotum naudinii leaf extract presented higher TPC (386.3 ± 9.7 mg GAE/g) and high antioxidant potential (CI50: 42.9 ± 1.2 µg/ mL), although statistically different from Trolox (36.6 ± 0.4 µg/mL). Mutisia mathewsii leaf extract reported higher TFC (175.6 ± 0.7 mg RUE/g) and Gaultheria glomerata fruit extract presented higher TAC (2340.0 ± 2.26 mg/g). It is concluded that the thirteen medicinal plants possess mostly flavonoids, phenols and/or tannins and have antioxidant potential directly proportional to the total phenol content.